Application of plasma-activated water (PAW) for mitigating methicillin-resistant Staphylococcus aureus (MRSA) on cooked chicken surface. (February 2021) - Wang, Jun; Han, Rongwei; Liao, Xinyu; Ding, Tian
Abstract: In recent years, antibiotic resistance has been a potential risk to public health. Cold plasma is an emerging non-thermal technology in food industry. Plasma-activated water (PAW) has been proposed as a novel chlorine-free disinfectant for food products in last decade. In this study, we employed PAW to inactivate methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-susceptible S. aureus (MSSA) on cooked chicken breast. The impacts of various factors on the bactericidal effects of PAW have been explored, including immersion times, treatment sequence, agitation and plasma-activated times for PAW. The use of 20-min plasma activated PAW with 20-min immersion could result in 2.09 ± 0.17 and 2.29 ± 0.04 log10 CFU/g reduction for MRSA and MSSA, respectively. Similar resistance of MRSA and MSSA to PAW exposure was observed. The PAW did not change the surface color of cooked chicken breast. In addition, MRSA and MSSA kinetics under the different treatments were fitted to Weibull model with well fitness and the results showed that the inactivation effect of PAW for MSSA was better than MRSA, regardless of treatment conditions. These results indicate PAW as an alternative disinfectant for cooked meat to assure microbiological safety and abate the dissemination of antibiotic resistance among food chain. Highlights: PAW as a chlorine-free disinfectant to inactivate S. aureus on chicken breast. MRSA and MSSA can be eliminated by over 99% with PAW treatment. The resistances of MRSA and MSSA to PAW show insignificant differences. PAW did not affect the surface color of chicken breast.